2015
DOI: 10.1364/oe.23.024648
|View full text |Cite
|
Sign up to set email alerts
|

Optical emission generated from silicon under dual-wavelength femtosecond double-pulse laser irradiation

Abstract: In femtosecond double-pulse laser-induced breakdown spectroscopy, collinear double-pulse performance is investigated experimentally using various laser wavelength combinations of 800 nm and 400 nm Ti: sapphire lasers. The induced plasma emission line collected by BK7 lenses is the Si (I) at 390.55 nm. The double-pulse time separation ranges from -300 ps to 300 ps. The line intensity is dependent on the time separation of the dual-wavelength femtosecond double-pulse, and its behavior is unlike that of single-wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…In addition, the emission intensity is proportional to the particle number density. 33 Therefore, the line intensity of Pb and Cr atoms is also proportional to C , which means, increasing the concentration of Pb and Cr is equivalent to increasing the emission of Pb and Cr atoms.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the emission intensity is proportional to the particle number density. 33 Therefore, the line intensity of Pb and Cr atoms is also proportional to C , which means, increasing the concentration of Pb and Cr is equivalent to increasing the emission of Pb and Cr atoms.…”
Section: Resultsmentioning
confidence: 99%
“…The plasma temperature was obtained by the Boltzmann plot and the plasma was in local thermodynamic equilibrium (LTE). The equation is as follows [41][42][43]:…”
Section: Resultsmentioning
confidence: 99%
“…For example, temporally shaped femtosecond double pulses were used to provide a path for the second pulse to interact with the ablation components excited by the first pulse, thereby facilitating the control of plume composition (atoms, ions, and nanoparticles). 19) The enhancement of plasma optical emission induced by double pulses has also been reported within femtosecond laser ablation of metals, 20,21) semiconductors, 22,23) and dielectrics 24) compared with that induced by single pulse with identical total energy. However, few studies have been reported on the shockwave expansion dynamics in doublepulse ablation.…”
mentioning
confidence: 79%